2019
DOI: 10.1016/j.molcel.2019.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Concerted 2-5A-Mediated mRNA Decay and Transcription Reprogram Protein Synthesis in the dsRNA Response

Abstract: Highlights d DsRNA rapidly arrests translation using 2-5A/RNase-Lmediated mRNA decay d Defense mRNAs preferentially accumulate due to positive feedback in the IFN response d RNase L-cleaved ribosomes are translationally competent d Human cells have RNase-L-inaccessible poly(A) + mRNA pools that are not translating

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 62 publications
2
66
1
Order By: Relevance
“…Furthermore, we have proposed that RNase L selectively degrades exogenous RNAs with Pelota-ABCE1 in a manner dependent on translation. Most recently, two reports have shown that under conditions that cells are treated with a potent trigger poly(I:C), RNase L degrades endogenous mRNAs, which is called 2-5A-mediated decay (2-5AMD) [31,32]. Interestingly, Rath et al demonstrated that RNase L activated by dsRNA degrades endogenous mRNAs, while RNase-L-resistant poly(A) + transcripts are enriched with noncoding RNAs, suggesting that RNase L sensitivity of RNA correlates with their translational activity [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have proposed that RNase L selectively degrades exogenous RNAs with Pelota-ABCE1 in a manner dependent on translation. Most recently, two reports have shown that under conditions that cells are treated with a potent trigger poly(I:C), RNase L degrades endogenous mRNAs, which is called 2-5A-mediated decay (2-5AMD) [31,32]. Interestingly, Rath et al demonstrated that RNase L activated by dsRNA degrades endogenous mRNAs, while RNase-L-resistant poly(A) + transcripts are enriched with noncoding RNAs, suggesting that RNase L sensitivity of RNA correlates with their translational activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, two reports have shown that under conditions that cells are treated with a potent trigger poly(I:C), RNase L degrades endogenous mRNAs, which is called 2-5A-mediated decay (2-5AMD) [31,32]. Interestingly, Rath et al demonstrated that RNase L activated by dsRNA degrades endogenous mRNAs, while RNase-L-resistant poly(A) + transcripts are enriched with noncoding RNAs, suggesting that RNase L sensitivity of RNA correlates with their translational activity [31]. The 2-5AMD is similar to the exogenous RNA decay in the sense that it seems to be dependent on 2-5A, RNase L and translation; however, in our condition that measures exogenous RNA decay, we detect specifically the degradation of exogenous RNA but can neither detect degradation of endogenous mRNAs nor rRNAs (e.g., Figure 2A, see GAPDH mRNA and rRNA).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two different laboratories made another important contribution to the understanding of how antiviral factors are preferentially produced in response to viral infections. They discovered that ribonuclease L (RNase L), which is activated in response to dsRNA, strongly depletes cellular mRNA pools through wide-spread mRNA degradation, but specifically leaves mRNAs encoding IFNs, cytokines, and other defense proteins intact [224][225][226]. The mechanism by which these mRNAs are excluded from RNase L-mediated cleavage remains unclear, but probably involves regulatory sequences, RNA secondary structures, and RBPs that protect individual mRNAs from degradation.…”
Section: Impact Of Stress Kinases On Innate Immune Signaling Pathwaysmentioning
confidence: 99%
“…Furthermore, response to polyI:C varies in cell-type dependent manner, levels of OAS isoforms as well as abundance of polyI:C-binding proteins in cells (62). Recent reports show the role of RNase L in widespread mRNA degradation and translation repression of select basal mRNAs while antiviral mRNAs escaped decay and robustly translated (63, 64). These results suggest that RNA signaling and decay pathways activated by RNase L are complex and the dyamics may vary based on specific activation of RNase L by 2-5A compared to indirect activation by polyI:C as well as cell type differences and abundance of dsRNA-binding proteins including OAS isoforms.…”
Section: Discussionmentioning
confidence: 99%